2015
DOI: 10.1093/nar/gkv410
|View full text |Cite
|
Sign up to set email alerts
|

Structural and sequencing analysis of local target DNA recognition by MLV integrase

Abstract: Target-site selection by retroviral integrase (IN) proteins profoundly affects viral pathogenesis. We describe the solution nuclear magnetic resonance structure of the Moloney murine leukemia virus IN (M-MLV) C-terminal domain (CTD) and a structural homology model of the catalytic core domain (CCD). In solution, the isolated MLV IN CTD adopts an SH3 domain fold flanked by a C-terminal unstructured tail. We generated a concordant MLV IN CCD structural model using SWISS-MODEL, MMM-tree and I-TASSER. Using the X-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(50 citation statements)
references
References 85 publications
(153 reference statements)
2
48
0
Order By: Relevance
“…The extent of central tDNA flexibility was moreover inversely proportional to TSD length. The examined viruses harbored a neutral, compact amino acid at the position analogous to Ala188 in PFV, and the polarity of the amino acid side chain correlated with the positioning of base preference significance relative to the points of vDNA insertion – a finding that was since confirmed by analyzing the behavior of mutants of the non-polar Pro187 side-chain in Mo-MLV IN (Aiyer et al, 2015). Taken together these studies imply that, though retroviral INs have structurally evolved to target unique nucleotide signatures, the common functional purpose of integration site base preferences may be to generate strand transfer-facilitating central tDNA distortion within the TCC.…”
Section: Mechanism Of Retroviral Tdna Base Preferencesmentioning
confidence: 81%
See 2 more Smart Citations
“…The extent of central tDNA flexibility was moreover inversely proportional to TSD length. The examined viruses harbored a neutral, compact amino acid at the position analogous to Ala188 in PFV, and the polarity of the amino acid side chain correlated with the positioning of base preference significance relative to the points of vDNA insertion – a finding that was since confirmed by analyzing the behavior of mutants of the non-polar Pro187 side-chain in Mo-MLV IN (Aiyer et al, 2015). Taken together these studies imply that, though retroviral INs have structurally evolved to target unique nucleotide signatures, the common functional purpose of integration site base preferences may be to generate strand transfer-facilitating central tDNA distortion within the TCC.…”
Section: Mechanism Of Retroviral Tdna Base Preferencesmentioning
confidence: 81%
“…This finding was in line with prior (Appa et al, 2001, Harper et al, 2001, Nowak et al, 2009) and subsequent (Demeulemeester et al, 2014) studies that implicated Ser119 in the process of HIV-1 tDNA site selection. The analogous residue in Mo-MLV IN, Pro187, plays the same role as Ala188 in PFV IN and Ser119 in HIV-1 in determining tDNA base selectivity (Aiyer et al, 2015). …”
Section: Mechanism Of Retroviral Tdna Base Preferencesmentioning
confidence: 99%
See 1 more Smart Citation
“…Initially identified by limited proteolysis of HIV-1 IN, 108 the domains were characterized in isolation using X-ray crystallography and/or nuclear magnetic resonance (NMR) spectroscopy (Figure 2a). 147153 The NTD folds into a compact three-helical bundle stabilized by coordination of a Zn 2+ ion by side chains of His and Cys residues comprising the invariant HHCC motif. 147,150 Often misidentified as a “zinc finger domain”, the NTD is most closely related to helix–turn–helix DNA binding domains.…”
Section: Structure Of Retroviral Inmentioning
confidence: 99%
“…1B, yellow) (12,23), and NMR studies of the MLV IN C-terminal domain revealed that this region is unstructured, suggesting a "fly-casting" mechanism for BET protein binding (23). Modifications to this region compromise MLV IN binding to BET proteins and alter MLV integration patterns (12,(23)(24)(25). In addition, the sequence of the ET domain is highly conserved (Fig.…”
Section: Significancementioning
confidence: 99%